The impact of postoperative glucocorticoids on complications after head and neck cancer surgery with free flap reconstruction: A retrospective study. - Tao Luo; Ren Zhou; Yu Sun (PLoS ONE)
Background After head and neck cancer surgery with free flap reconstruction, the use of glucocorticoids is often required to alleviate inflammation and edema. However, the impact of glucocorticoid on postoperative complications and cancer progression remains unclear. Methods This retrospective cohort study included 711 elderly patients who underwent head and neck cancer surgery with free flap reconstruction at Shanghai Ninth People's Hospital from January 1, 2014, to December 31, 2022. Patients were categorized based on postoperative glucocorticoid usage into a high-dose steroid group (n = 307) and a control group (n = 404). The study focused on the impact of postoperative GC use on postoperative complications and long-term oncological outcomes. Results Multivariate analysis indicated that compared to the control group, the high-dose steroid group had a significant increase in postoperative complications, including atelectasis (OR: 3.83, 95% CI: 1.27-14.11, P = 0.025), postoperative hyperglycemia (OR: 1.54, 95% CI: 1.14-2.08, P = 0.006), and flap complications (OR: 4.61, 95% CI: 3.31-6.47, P < 0.001). These complications often required extended hospital stays (β: 1.656, 95% CI: 1.075-2.236, P <  0.001). Additionally, the high-dose steroid group had a higher rate of unplanned readmissions within one year (OR: 5.61, 95% CI: 3.87-8.25, P < 0.001). The increased readmission rates were notably due to difficulties swallowing requiring percutaneous gastrostomy (OR: 3.62, 95% CI: 1.97-6.98, P < 0.001), recurrence (OR: 9.34, 95% CI: 5.02-19.05, P < 0.001), and metastasis (OR: 4.78, 95% CI: 2.58-9.44, P < 0.001). Conclusion The use of high-dose postoperative glucocorticoids is associated with increased postoperative complications, higher readmission rates, and poorer oncological outcomes in patients. The results advocate for cautious use and dosage management of perioperative glucocorticoids in head and neck surgeries to optimize patient outcomes.